Influencing factors of green energy transition: The role of economic policy uncertainty, technology innovation, and ecological governance in China - Yu, Zhichao; Guo, XiaoDi (Frontiers in Environmental Science, 2023)
For environmental sustainability and resource security global energy system requires a revolutionary transition from traditional energy to green energy resources. Therefore, this study investigates the influence of economic policy uncertainty, technological innovation, ecological governance, and economic growth on the green energy transition in China. We employed Bootstrap Auto-regressive Distributive Lag (BARDL) model to evaluate the long-run association between the study variables from Q1-2000 to Q4-2020. The preliminary finding confirms the long-run cointegration relationship among model variables. The results show that economic policy uncertainty and economic growth negatively derive green energy transition in the long-run. In contrast, technology innovation and environmental governance positively influence the green energy transition. These findings propose strengthening the environmental governance mechanism and technology innovation to accelerate the green energy transition in China.